A review of the impact of PBL on pre-service teachers’ Learning - Borhan, Mohamad Termizi (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Inspired by positive results of Problem Based Learning (PBL) implementation within an array of disciplines, PBL was also implemented in teacher education fields since 1980’s. Since then, the literature of PBL implementation and its impact teacher education have been growing. However, there was no review work reported to conclude on how PBL impact specific learning outcomes in teacher education. Hence the aim of the paper was to review the research evidences concerning the impact of PBL implementation focusing on pre-service teachers´ knowledge and skills. Resources (journal articles and paper proceedings) were obtained from bibliographic databases and key research journals. The resources were chosen based on specific inclusion criteria, followed by a common review framework to ensure commonality and comprehensiveness during the review. The review works concluded that a PBL experience within teacher education provided opportunities for pre-service teachers to simultaneously acquire knowledge and to develop skills deemed important for the future teachers. This information is important to further refine PBL employment especially in teacher education, and to contemplate rooms for improvement, which will subsequently lead to an improved constructivism learning experience for pre-service teachers.